A commentary after 38 years - Alfred Sohn-Rethel: translators’ introduction - Burnfin, Daniel; Schlaudt, Oliver (Historical materialism, 2020)
"A Commentary after 38 Years - Alfred Sohn-Rethel" published on 01 Dec 2020 by Brill